Amplification of pvmdr1 associated with multidrug-resistant Plasmodium vivax. - Suwanarusk, R; Chavchich, M; Russell, B; Jaidee, A; Chalfein, F; Barends, M; Prasetyorini, B; Kenangalem, E; Piera, K; Lek-Uthai, U; Anstey, N; Tjitra, E; et al. (2008)
BACKGROUND: Multidrug-resistant strains of Plasmodium vivax are emerging in Southeast Asia. METHODS: In vitro drug susceptibility and pvmdr1 genotype were determined in P. vivax field isolates from Indonesia and Thailand. RESULTS: Increased pvmdr1 copy number was present in 21% of isolates from Thailand (15/71) and none from Indonesia (0/114; P < .001). Compared with Indonesian isolates, the median IC(50) of Thai isolates was lower for chloroquine (36 vs. 114 nmol/L; P < .001) but higher for amodiaquine (34 vs. 13.7 nmol/L; P = .032), artesunate (8.33 vs. 1.58 nmol/L; P < .001), and mefloquine (111 vs. 9.87 nmol/L; P < .001). In 11 cryopreserved Thai isolates, those with increased pvmdr1 copy number had a higher IC(50) for mefloquine (78.6 vs. 38 nmol/L for single-copy isolates; P = .006). Compared with isolates with the wild-type allele, the Y976F mutation of pvmdr1 was associated with reduced susceptibility to chloroquine (154 nmol/L [range, 4.6-3505] vs. 34 nmol/L [range, 6.7-149]; P < .001) but greater susceptibility to artesunate (1.8 vs. 9.5 nmol/L; P = .009) and mefloquine (14 vs. 121 nmol/L; P < .001). CONCLUSIONS: Amplification of pvmdr1 and single-nucleotide polymorphisms are correlated with susceptibility of P. vivax to multiple antimalarial drugs. Chloroquine and mefloquine appear to exert competitive evolutionary pressure on pvmdr1, similar to that observed with pfmdr1 in Plasmodium falciparum.